Law and Economics of Public Procurement Reforms - Piga, Gustavo; Tatrai, Tunde (London : Taylor and Francis, 2017)
"Appropriate laws and regulations are essential tools to direct the action of procurers toward the public good and avoid corruption and misallocation of resources. Common laws and regulations across regions, nations and continents potentially allow for the further opening of markets and ventures to newcomers and new ideas to satisfy public demand. Law and Economics of Public Procurement Reforms collects the original contributions related to the new European Union Directives approved in 2014 by the EU Parliament. They are of both economists and lawyers, and have been presented in a manner that allows for exchanges of views and "real time" interaction. This book features, for each section, an introductory exchange between two experts of different disciplines, made up of a series of sequential interactions between an economist and a lawyer, which enriches the liveliness of the debate and improve the mutual understanding between the two professions. Four sections characterize this book: Supporting social considerations via public procurement; Green public procurement; Innovation through innovative partnerships; and Lots - The Economic and Legal Challenges of Centralized Procurement. These themes have current relevance of the new European Public Procurement Directives. Written by an impressive array of experts in their respected fields, this volume is of great importance to practitioners who work in the field of EU public procurement in the Member States of the EU, as well as academics and students who study public finance, public policy and regulation. "--Provided by publisher.
r SHARLENE JO-ANN SHILLINGFORD MCKLMON AND SHIRLEY -- chapter 3 Local preferences as non-discriminatory instrument in public procurement of fresh foods: why, when and how / BOSTJAN FERK -- part Part 2 Joint public procurement -- chapter 4 Colloquium / NICOLA DIMITRI -- chapter 5 Addressing in part market imbalances in the pharmaceutical sector through voluntary joint public procurement / ANTOINETTE CALLEJA -- chapter 6 Joint procurement and the EU perspective / FRANCESCO SAVERIO MENNINI, NICOLA DIMITRI, LARA GITTO, -- part Part 3 Big Data in public procurement -- chapter 7 Colloquium / MIHALY FAZEKAS -- chapter 8 Open Data and procurement / BERNARDO NICOLETTI -- r
Keywords: Europe -- European Union countries; Government purchasing; Government purchasing -- Law and legislation; Public Finance; Public Policy; Regulation; BUSINESS & ECONOMICS / Public Finance